Cancer stem cell marker expression and methylation status in patients with colorectal cancer - Mersakova, Sandra; Janikova, Katarina; Kalman, Michal; Marcinek, Juraj; Grendar, Marian; Vojtko, Martin; Kycina, Roman; Pindura, Miroslav; Janik, Jan; Mikolajcik, Peter; Gabonova, Eva; Laca, Ludovit; et al. (Oncology letters, 2022)
The number of individuals diagnosed with colorectal cancer (CRC) has been on an alarming upward trajectory over the past decade. In some countries, this cancer represents one of the most frequently diagnosed types of neoplasia. Therefore, it is an important demand to study the pathology underlying this disease to gain insights into the mechanism of resistance to treatment. Resistance of tumors to chemotherapy and tumor aggressiveness have been associated with a minor population of neoplastic cells, which are considered to be responsible for tumor recurrence. These types of neoplastic cells are known as cancer stem cells, which have been previously reported to serve an important role in pathogenesis of this malignant disease. Slovakia has one of the highest incidence rates of CRC worldwide. In the present study, the aim was to classify the abundance of selected stem cell markers (CD133, CD166 and Lgr5) in CRC tumors using flow cytometry. In addition, the methylation status of selected genomic regions of CRC biomarkers (ADAMTS16, MGMT, PROM1 (CD133), LGR5 and ALCAM) was investigated by pyrosequencing in a cohort of patients from Martin University Hospital, Martin, Slovakia. Samples from both primary tumors and metastatic tumors were tested. Analysis of DNA methylation in the genomic regions of indicated five CRC biomarkers was also performed, which revealed the highest levels of methylation in the A disintegrin and metalloproteinase with thrombospondin motifs 16 and O6-methyguanine-DNA methyl transferase genes, whereas the lowest levels of methylation were found in genes expressing prominin-1, leucine-rich repeat-containing G-protein-coupled receptor 5 and activated leukocyte cell adhesion molecule. Furthermore, tumor tissues from metastases showed significantly higher levels of CD133+ cells compared with that in primary tumors. Higher levels of CD133+ cells correlated with TNM stage and the invasiveness of CRC into the lymphatic system. Although relatively small number of samples was processed, CD133 marker was consider to be important marker in pathology of CRC.
Keywords: pyrosequencing and DNA methylation; cancer stem cells; CD surface markers; colorectal cancer; flow cytometry